Sandwich membrane electrode for realizing functional gradient regulation and control through carbon carrier morphology control and preparation method of sandwich membrane electrode
By using a carbon support catalytic layer regulated by functional gradient in the membrane electrode, the problems of low mass transfer rate and gas transmission efficiency of traditional membrane electrodes are solved, and higher catalyst utilization and durability are achieved.
Patent Information
- Application Number
- CN202411869853.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The distribution of single catalytic layer of traditional membrane electrodes leads to low mass transfer rate and gas transfer efficiency, low catalyst utilization and poor durability.
Functional gradient control of the sandwich electrode is achieved through carbon support morphology control, at least two catalytic layers are designed for each anode and cathode. The size of the carbon support is gradually reduced or increased or interlaced, and the noble metal catalyst is supported by a carbon support, combined with perfluorosulfonic acid resin to optimize the uniformity of the catalyst slurry and spraying effect.
The mass transfer rate and gas transmission efficiency between the proton exchange membrane and the catalytic layer are improved, the electrical stability of the membrane electrode is enhanced, and the utilization rate and durability of precious metals are improved.
Smart Images

Figure CN119663333A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of water electrolysis, specifically relating to a sandwich membrane electrode with functional gradient regulation achieved by controlling the morphology of a carbon support and its preparation method. Background Art
[0002] Hydrogen production through water electrolysis is currently the most promising technology for producing green energy, with a wide range of applications, primarily in the energy, chemical, and transportation sectors. In the energy sector, it can serve as an important storage and conversion method for renewable energy, providing a stable and adjustable energy output for the power system. In the chemical sector, it can be used to produce chemicals such as hydrogen and ammonia, offering advantages such as environmental friendliness and high efficiency. In the transportation sector, it can serve as a crucial energy source for fuel cell vehicles, enabling zero-emission and high-efficiency travel. Membrane electrode technology plays a vital role in the field of electrochemical energy conversion, and its development and optimization are of great significance for improving energy conversion efficiency, reducing costs, and promoting the application of clean energy technologies.
[0003] In water electrolysis for hydrogen production, the membrane electrode assembly (MEA) is a crucial component, involving three-phase interfacial reactions and complex mass and heat transfer processes. Its main components include a proton exchange membrane, a catalyst layer, and a diffusion layer. Among these, the catalyst layer, as the site of electrochemical reactions, has a decisive impact on MEA performance. Besides reducing the catalyst loading, optimizing and designing the catalyst structure is also an effective strategy for improving the overall performance of the MEA.
[0004] Traditional membrane electrodes used in water electrolysis suffer from low mass transfer rates and gas transport efficiency due to their single catalyst layer distribution, resulting in low catalyst utilization, slow reaction rates, and poor durability. Furthermore, the prepared catalyst layer exhibits poor proton conductivity, and the transport resistance of multilayered catalyst layers increases significantly. Therefore, developing a novel functionally graded membrane electrode is essential. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention optimizes and designs the structure of the catalytic layer based on a single-layer membrane electrode, solving the problems of low mass transfer rate and gas transport efficiency in conventional membrane electrodes due to their single catalytic layer distribution, leading to low catalyst utilization and poor durability. This invention provides a sandwich membrane electrode with functionally graded modulation achieved by controlling the morphology of a carbon support and its preparation method. The sandwich membrane electrode prepared using this invention improves the mass transfer rate and gas transport efficiency between the proton exchange membrane and the catalytic layer, enhancing the electrical stability of the sandwich membrane electrode.
[0006] To achieve the above objectives, the first aspect of the present invention discloses a sandwich membrane electrode that achieves functional gradient modulation by controlling the morphology of a carbon support.
[0007] The sandwich membrane electrode includes a proton exchange membrane and a catalyst layer attached to both sides of the proton exchange membrane.
[0008] The catalyst layer is attached to each side of the proton exchange membrane and comprises at least two layers and at most five layers; in the direction away from the proton exchange membrane, the carbon support size of the catalyst layer gradually decreases, or gradually increases, or the sizes are staggered.
[0009] The catalyst layer comprises a noble metal catalyst and a perfluorosulfonic acid resin, wherein the noble metal catalyst is synthesized by supporting noble metal nanoparticles on a carbon support.
[0010] Preferably, the carbon support has a regular hexagonal three-dimensional structure.
[0011] Preferably, the carbon support has a size of 5µm-100nm.
[0012] Preferably, the noble metal is Pt nanoparticles.
[0013] Preferably, the loading of the noble metal nanoparticles is 5-50%.
[0014] The second aspect of this invention discloses a method for preparing the above-mentioned sandwich film electrode, which specifically includes the following steps:
[0015] (1) A catalyst slurry is prepared using a catalyst synthesized by loading noble metal nanoparticles onto a carbon support, wherein the raw materials are as follows: by mass fraction, the content of noble metal catalyst is 5%-10%, the content of perfluorosulfonic acid resin is 0.1%-10%, and the remainder is made up with isopropanol and deionized water and mixed evenly, wherein the ratio of isopropanol to deionized water is 0.5-16.
[0016] The raw material is subjected to high-speed shearing in a low-temperature water environment for 0.5-1.5 hours, and then subjected to ultrasonic treatment in a low-temperature water environment for 0.5-1.5 hours to obtain the catalyst slurry.
[0017] (2) The catalyst slurry obtained in step (1) is sprayed onto the cathode side of the proton exchange membrane (PEM) using a spraying machine, with a spraying loading of 0.6-2.0 mg / cm³. 2 After drying, a catalyst layer is obtained;
[0018] (3) Increase the number of catalyst layers on the cathode side of the proton exchange membrane (PEM) and repeat steps (1)-(2);
[0019] (4) Preparation of the catalyst layer on the anode side of the proton exchange membrane (PEM) is obtained by repeating steps (1)-(3).
[0020] Preferably, the catalyst feedstock for the anode side of the proton exchange membrane is commercially available Umicore Ir75-0480 catalyst, with a coating loading of 0.75 mg / cm³.2 .
[0021] The third aspect of this invention discloses the application of the above-mentioned sandwich membrane electrodes as water electrolysis membrane electrodes.
[0022] Compared with the prior art, the beneficial effects of this invention are as follows:
[0023] This invention employs effective control of carbon supports of different sizes to design a functionally graded sandwich membrane electrode, with both the anode and cathode comprising at least two catalytic layers. The catalytic layers were optimized in terms of precious metal loading, resin content, catalyst particle size, and dispersion process. This optimization ensures the uniformity of the catalyst slurry and a good spraying effect. This improves upon the low mass transfer rate and gas transport efficiency, increases the utilization rate of precious metals, and enhances its durability. Attached Figure Description
[0024] Figure 1 A schematic diagram of sandwich electrode fabrication;
[0025] Figure 2 SEM images of carbon supports 1-5;
[0026] Figure 3 A schematic diagram of the sandwich membrane electrode prepared in Example 1;
[0027] Figure 4 A schematic diagram of the sandwich membrane electrode prepared in Example 2;
[0028] Figure 5 A schematic diagram of the sandwich membrane electrode prepared in Example 3. Detailed Implementation
[0029] The technical solution of the present invention will be described in detail below with reference to the accompanying drawings and embodiments, but this does not limit the present invention to the scope of the described embodiments. Process parameters not specified in the embodiments of this application can be performed according to conventional methods, and all raw materials used can be obtained through commercial channels.
[0030] Example 1
[0031] (1) Preparation of the first catalyst sublayer: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 1, wherein: the noble metal catalyst content was 5%; the ratio of isopropanol to deionized water was 0.5; the perfluorosulfonic acid resin content was 0.1%; the slurry was subjected to high-speed shearing in a low-temperature water environment for 0.5 h, followed by ultrasonication in a low-temperature water environment for 0.5 h, and then sprayed onto the cathode side of the proton exchange membrane (PEM) using a sprayer, with a coating loading of 0.6 mg / cm³. 2 After drying, the first catalytic sublayer is obtained;
[0032] (2) Preparation of the second catalyst sublayer: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 2, wherein: the noble metal catalyst content was 5%; the ratio of isopropanol to deionized water was 1.5; the perfluorosulfonic acid resin content was 1%; the slurry was subjected to high-speed shearing in a low-temperature aquatic environment for 0.7 h, followed by ultrasonication in a low-temperature aquatic environment for 0.7 h, and then sprayed onto the first catalyst sublayer using a spraying machine with a coating loading of 0.7 mg / cm³. 2 After drying, the second catalyst sublayer is obtained;
[0033] (3) Preparation of the third catalyst sublayer: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 3, wherein: the noble metal catalyst content was 5%; the ratio of isopropanol to deionized water was 2.5; the perfluorosulfonic acid resin content was 3%; the slurry was subjected to high-speed shearing in a low-temperature aquatic environment for 0.9 h, followed by ultrasonication in a low-temperature aquatic environment for 0.9 h, and then sprayed onto the second catalyst sublayer using a spraying machine with a coating loading of 0.8 mg / cm³. 2 After drying, the third catalytic sublayer is obtained;
[0034] (4) Preparation of the fourth catalyst sublayer: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 4, wherein: the noble metal catalyst content was 5%; the ratio of isopropanol to deionized water was 3.5; the perfluorosulfonic acid resin content was 5%; the slurry was subjected to high-speed shearing in a low-temperature water environment for 1.1 h, followed by ultrasonication in a low-temperature water environment for 1.1 h, and then sprayed onto the third catalyst sublayer using a spraying machine with a coating loading of 0.9 mg / cm³. 2 After drying, the fourth catalytic sublayer is obtained;
[0035] (5) Preparation of the fifth catalyst sublayer: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 5, wherein: the noble metal catalyst content was 5%; the ratio of isopropanol to deionized water was 4.5; the perfluorosulfonic acid resin content was 7%; the slurry was subjected to high-speed shearing in a low-temperature water environment for 1.3 h, followed by ultrasonication in a low-temperature water environment for 1.3 h, and then sprayed onto the fourth catalyst sublayer using a spraying machine with a coating loading of 1.0 mg / cm³. 2 After drying, the fifth catalyst sublayer is obtained;
[0036] (6) Preparation of the anode side catalyst layer: Repeat steps (1)-(5) above.
[0037] Example 2
[0038] (1) Preparation of the first catalyst sublayer: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 5, wherein: the noble metal catalyst content was 8%; the ratio of isopropanol to deionized water was 5.5; the perfluorosulfonic acid resin content was 9%; the slurry was subjected to high-speed shearing in a low-temperature water environment for 0.6 h, followed by ultrasonication in a low-temperature water environment for 0.6 h, and then sprayed onto the cathode side of the proton exchange membrane (PEM) using a sprayer, with a coating loading of 1.5 mg / cm³. 2 After drying, the first catalytic sublayer is obtained;
[0039] (2) Preparation of the second catalyst sublayer: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 4, wherein: the noble metal catalyst content was 8%; the ratio of isopropanol to deionized water was 6.5; the perfluorosulfonic acid resin content was 7%; the slurry was subjected to high-speed shearing in a low-temperature aquatic environment for 0.8 h, followed by ultrasonication in a low-temperature aquatic environment for 0.8 h, and then sprayed onto the first catalyst sublayer using a spraying machine with a coating loading of 1.4 mg / cm³. 2 After drying, the second catalyst sublayer is obtained;
[0040] (3) Preparation of the third catalyst sublayer: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 3, wherein: the noble metal catalyst content was 8%; the ratio of isopropanol to deionized water was 7.5; the perfluorosulfonic acid resin content was 5%; the slurry was subjected to high-speed shearing in a low-temperature water environment for 1.0 h, followed by ultrasonication in a low-temperature water environment for 1.0 h, and then sprayed onto the second catalyst sublayer using a spraying machine with a coating loading of 1.3 mg / cm³. 2 After drying, the third catalytic sublayer is obtained;
[0041] (4) Preparation of the fourth catalyst sublayer: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 2, wherein: the noble metal catalyst content was 8%; the ratio of isopropanol to deionized water was 8.5; the perfluorosulfonic acid resin content was 3%; the slurry was subjected to high-speed shearing in a low-temperature water environment for 1.2 h, followed by ultrasonication in a low-temperature water environment for 1.2 h, and then sprayed onto the third catalyst sublayer using a spraying machine with a coating loading of 1.2 mg / cm³. 2 After drying, the fourth catalytic sublayer is obtained;
[0042] (5) Preparation of the fifth catalyst sublayer: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 1, wherein: the noble metal catalyst content was 8%; the ratio of isopropanol to deionized water was 9.5; the perfluorosulfonic acid resin content was 0.2%; the slurry was subjected to high-speed shearing in a low-temperature water environment for 1.2 h, followed by ultrasonication in a low-temperature water environment for 1.2 h, and then sprayed onto the fourth catalyst sublayer using a spraying machine with a coating loading of 1.1 mg / cm³. 2 After drying, the fifth catalyst sublayer is obtained;
[0043] (6) Preparation of the anode side catalyst layer: Repeat steps (1)-(5) above.
[0044] Example 3
[0045] (1) Preparation of the first catalyst sublayer: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 1, wherein: the noble metal catalyst content was 10%; the ratio of isopropanol to deionized water was 10.5; the perfluorosulfonic acid resin content was 0.5%; the slurry was subjected to high-speed shearing in a low-temperature water environment for 0.5 h, followed by ultrasonication in a low-temperature water environment for 0.5 h, and then sprayed onto the cathode side of the proton exchange membrane (PEM) using a spraying machine, with a spraying loading of 1.6 mg / cm³. 2 After drying, the first catalytic sublayer is obtained;
[0046] (2) Preparation of the second catalyst sublayer: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 5, wherein: the noble metal catalyst content was 10%; the ratio of isopropanol to deionized water was 12.5; the perfluorosulfonic acid resin content was 4%; the slurry was subjected to high-speed shearing in a low-temperature aquatic environment for 0.75 h, followed by ultrasonication in a low-temperature aquatic environment for 0.75 h, and then sprayed onto the first catalyst sublayer using a spraying machine with a coating loading of 1.7 mg / cm³. 2 After drying, the second catalyst sublayer is obtained;
[0047] (3) Preparation of the third catalyst sublayer: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 2, wherein: the noble metal catalyst content was 10%; the ratio of isopropanol to deionized water was 14.5; the perfluorosulfonic acid resin content was 6%; the slurry was subjected to high-speed shearing in a low-temperature water environment for 1.0 h, followed by ultrasonication in a low-temperature water environment for 1.0 h, and then sprayed onto the second catalyst sublayer using a spraying machine with a coating loading of 1.8 mg / cm³. 2 After drying, the third catalytic sublayer is obtained;
[0048] (4) Preparation of the fourth catalyst sublayer: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 4, wherein: the noble metal catalyst content was 10%; the ratio of isopropanol to deionized water was 15; the perfluorosulfonic acid resin content was 8%; the slurry was subjected to high-speed shearing in a low-temperature water environment for 1.25 h, followed by ultrasonication in a low-temperature water environment for 1.25 h, and then sprayed onto the third catalyst sublayer using a spraying machine with a coating loading of 1.9 mg / cm³. 2 After drying, the fourth catalytic sublayer is obtained;
[0049] (5) Preparation of the fifth catalyst sublayer: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 3, wherein: the noble metal catalyst content was 10%; the ratio of isopropanol to deionized water was 1:6; the perfluorosulfonic acid resin content was 10%; the slurry was subjected to high-speed shearing in a low-temperature water environment for 1.5 h, followed by ultrasonication in a low-temperature water environment for 1.5 h, and then sprayed onto the fourth catalyst sublayer using a spraying machine with a coating loading of 2.0 mg / cm³. 2 After drying, the fifth catalyst sublayer is obtained;
[0050] (6) Preparation of the anode side catalyst layer: Repeat steps (1)-(5) above.
[0051] Comparative Example 1
[0052] (1) Preparation of a single-layer catalytic membrane electrode: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 1. The noble metal catalyst content was 1%; the ratio of isopropanol to deionized water was 0.1; and the perfluorosulfonic acid resin content was 12%. The slurry was subjected to high-speed shearing in a low-temperature water environment for 0.1 h, followed by ultrasonication in a low-temperature water environment for 0.1 h. The slurry was then sprayed onto the cathode side of a proton exchange membrane (PEM) using a sprayer, with a coating loading of 0.1 mg / cm³. 2 After drying, a single-catalytic-layer membrane electrode is obtained;
[0053] (2) Preparation of the anode side catalyst layer: Repeat step (1) above.
[0054] Comparative Example 2
[0055] (1) Preparation of a single-layer catalytic membrane electrode: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 1. The noble metal catalyst content was 2%; the ratio of isopropanol to deionized water was 0.3; and the perfluorosulfonic acid resin content was 14%. The slurry was subjected to high-speed shearing in a low-temperature water environment for 0.3 h, followed by ultrasonication in a low-temperature water environment for 0.3 h. The slurry was then sprayed onto the cathode side of a proton exchange membrane (PEM) using a sprayer, with a coating loading of 0.3 mg / cm³. 2 After drying, a single-catalytic-layer membrane electrode is obtained;
[0056] (2) Preparation of the anode side catalyst layer: Repeat step (1) above.
[0057] Comparative Example 3
[0058] (1) Preparation of a single-layer catalytic membrane electrode: A catalyst slurry was prepared using noble metal nanoparticles supported on carbon support No. 1. The noble metal catalyst content was 3%; the ratio of isopropanol to deionized water was 1:8; and the perfluorosulfonic acid resin content was 16%. The slurry was subjected to high-speed shearing in a low-temperature water environment for 1.8 h, followed by ultrasonication in a low-temperature water environment for 1.8 h. The slurry was then sprayed onto the cathode side of the proton exchange membrane (PEM) using a sprayer, with a coating loading of 2.5 mg / cm³. 2 After drying, a single-catalytic-layer membrane electrode is obtained;
[0059] (2) Preparation of the anode side catalyst layer: Repeat step (1) above.
[0060] Comparative Example 4
[0061] The preparation method is the same as in Example 1, except that the content of the noble metal catalyst, the ratio of isopropanol to deionized water, and the content of perfluorosulfonic acid resin in the catalyst slurry are as follows: the content of the noble metal catalyst is 5%; the ratio of isopropanol to deionized water is 0.5; and the content of perfluorosulfonic acid resin is 0.1%.
[0062] Comparative Example 5
[0063] The preparation method is the same as in Example 1, except that the carbon support type used is carbon support No. 5.
[0064] The stability of the membrane electrodes prepared in Examples 1-3 and Comparative Examples 1-5 was analyzed, and the results are shown in Table 1.
[0065] Table 1
[0066]
[0067]
[0068] Impedance analysis was performed on the membrane electrodes prepared in Examples 1-3 and Comparative Examples 1-5, as shown in Table 2.
[0069] Table 2
[0070]
[0071] As shown in Tables 1 and 2, the carbon support morphology control strategy for preparing functionally graded membrane electrodes has significant effects. The reason for this is:
[0072] First, the carbon support of the present invention has adjustable surface size, high specific surface area, hierarchical pore structure and low charge transfer resistance, indicating that it can effectively improve mass transfer efficiency, while having excellent noble metal particle loading capacity.
[0073] Second, compared to single-layer membrane electrodes, the gradient design of the membrane electrode of this invention is beneficial to improving mass transfer rate and gas transport efficiency. The specific reasons are as follows:
[0074] 1) The noble metal loading is highest near the proton exchange membrane (PEM) side, decreasing outwards. This design is because a large number of hydrogen ions participate in the reaction at the PEM side, requiring numerous active sites. The high loading at the innermost side satisfies these site requirements. As hydrogen ions decrease further outwards due to the reaction during transport, only a small amount of noble metal is needed. This design increases the number of active sites required for the reaction while reducing the use of excess noble metal, thus improving noble metal utilization.
[0075] 2) The resin content is highest near the proton exchange membrane (PEM) side, decreasing outwards. This design is because the large amount of hydrogen ions generated on the PEM side requires extremely rapid transport to the catalyst surface for reaction, and the high resin content provides numerous transport channels for hydrogen ion transfer, thus meeting the reaction requirements. Therefore, this design can effectively improve the mass transfer rate during the reaction process.
[0076] 3) The carbon support used near the proton exchange membrane (PEM) side is the smallest, with the size gradually increasing from the PEM side outwards. This design is because the hydrogen ions participating in the reaction at the PEM side generate a large amount of hydrogen gas. The small-sized carbon support has a high specific surface area and hierarchical pore structure, which allows for rapid gas transport, thus ensuring the orderly progress of the reaction. The amount of gas generated decreases from the inside out, which can be achieved by using carbon supports with smaller specific surface areas and larger sizes. On the other hand, the gradient design of the carbon support size increasing from the inside out can also prevent the loss of precious metal particles caused by water and gas flow during the reaction. The outer layer of large-sized carbon support can achieve the secondary utilization of precious metals and increase the utilization rate of precious metals, thereby improving their durability.
[0077] Third, this invention adjusts the ratio of alcohol, water, and resin in the slurry, which further enhances the proton conductivity of the cathode catalyst layer, thereby reducing the transport resistance of the membrane electrode. This results in excellent stability of the membrane electrode. Therefore, the carbon support morphology control of this invention to achieve functionally graded sandwich membrane electrodes and its preparation method have beneficial effects on improving membrane electrode performance.
[0078] This invention is not limited to the above-described embodiments. Any changes in shape or structure are within the scope of protection of this invention. The scope of protection of this invention is defined by the appended claims. Those skilled in the art can make various changes, modifications, substitutions, combinations, and simplifications to these embodiments without departing from the principles and essence of this invention. All such changes and simplifications should be considered equivalent substitutions and fall within the scope of protection of this invention.
Claims
1. A sandwich membrane electrode, characterized in that: Functional gradient regulation can be achieved through carbon carrier morphology control; The sandwich membrane electrode comprises a proton exchange membrane and a catalyst layer attached to both sides of the proton exchange membrane; The catalyst layer is attached to each side of the proton exchange membrane and includes at least two layers and at most five layers; in the direction away from the proton exchange membrane, the size of the carbon carrier of the catalyst layer gradually decreases, or gradually increases, or the size is staggered; The catalytic layer comprises a noble metal catalyst and a perfluorosulfonic acid resin, wherein the noble metal catalyst is synthesized by carbon carrier-supported noble metal nanoparticles.
2. A sandwich membrane electrode according to claim 1, characterized in that: The carbon carrier has a regular hexagonal three-dimensional structure.
3. The sandwich membrane electrode according to claim 1, characterized in that: The carbon carrier has a size of 5um-100nm.
4. The sandwich membrane electrode according to claim 1, characterized in that: The noble metal is Pt nanoparticles.
5. The sandwich membrane electrode according to claim 1, characterized in that: The loading amount of the noble metal nanoparticles is 5-50%.
6. The method for preparing a sandwich membrane electrode according to any one of claims 1 to 5, characterized in that: The specific steps include: (1) A catalyst slurry is prepared using a catalyst synthesized by using carbon carrier-supported precious metal nanoparticles, wherein the raw materials are as follows: by mass fraction, the precious metal catalyst content is 5%-10%, the perfluorosulfonic acid resin content is 0.1%-10%, and the rest is supplemented with isopropanol and deionized water and mixed evenly, wherein the ratio of isopropanol to deionized water is 0.5-16; The raw materials are placed in a low-temperature water environment for high-speed shearing for 0.5-1.5 hours, and then placed in a low-temperature water environment for ultrasonic treatment for 0.5-1.5 hours to obtain a catalyst slurry; (2) Use a sprayer to spray the catalyst slurry obtained in step (1) onto the cathode side of the proton exchange membrane, with a spray loading of 0.6-2.0 mg / cm 2 , and dried to obtain a catalytic layer; (3) Repeat steps (1) to (2) to increase the number of catalyst layers on the cathode side of the proton exchange membrane; (4) The catalyst layer on the anode side of the proton exchange membrane is prepared by repeating steps (1) to (3).
7. The preparation method according to claim 6, characterized in that: The raw materials for the catalyst layer on the anode side of the proton exchange membrane are all commercial Umicore Ir75-0480 catalysts, with a spray loading of 0.75 mg / cm 2 .
8. The sandwich membrane electrode as described in any one of claims 1 to 5 is used as a membrane electrode for water electrolysis.